Physical and antioxidant properties of starch/gelatin films incorporated with Garcinia atroviridis leaves - I. S., Nur Amila Najwa; Guerrero, P.; K., de la Caba; Z.A., Nur Hanani (Elsevier, 2020)
The potential application of Garcinia atroviridis leaves (GAL) extract as an active compound in tapioca starch/gelatin films for natural-based food packaging was studied in this work. Films with different concentrations of GAL extract (1, 3 and 5 %) were prepared by solution casting and the obtained films were homogenous, as observed by scanning electron microscopy (SEM). Regarding mechanical properties, tensile strength (TS) and elongation at break (EAB) increased with GAL concentration, leading to stronger and more flexible films. Furthermore, a higher level of GAL reduced water solubility. Additionally, DPPH radical scavenging assay showed that the antioxidant properties of the films were improved with the addition of GAL extract. Therefore, GAL extract incorporated into film-forming formulations showed potential as antioxidant additive. However, future research is essential to assess the shelf-life extension for various types of food products.